Optimal Structural Parametric Design of Permanent Magnet Eddy-current Couplers Based on the Dimensional Analysis Method - Yang Chaojun; Ma Chao; Gu Lixiang; Sun Xianyou; Liang Xinghai; Wang Jian (Jixie chuandong)
In light of the problem of complex and diverse parameters and low optimization efficiency in the performance optimization of a solid disk permanent magnet eddy-current coupler, the dimensionless parameters of the disk permanent magnet eddy-current coupler were derived according to the dimensional analysis method. Six dimensionless parameters such as velocity parameter, magnetic density parameter, air gap parameter and dimensionless number of main dimensions were obtained, which effectively reduced the workload of the analytical study; the correctness of dimensionless numbers was verified by the equation analysis method. The impact of each dimensionless number on the output torque of the permanent magnet eddy-current coupler was simulated by the 3D finite element. In order to improve the optimization efficiency, the structural optimization design was carried out by the response surface method to improve the utilization of permanent magnets, and the simulation results verified the effectiveness of the optimization.